Continuous Coordinated Universal Time adopted by the ITU - Achkar, J. (2025)
The work reported here is one of the activities of the International Telecommunication Union - Radiocommunication Sector (ITU-R) Study Group 7 (SG 7) (Science Services), Working Party 7A (WP 7A) (Time Signals and Frequency Standard Emissions). As a result of technical time scale issues raised by Sector Members of the ITU-R. about thirty years ago and a letter from the Director of the Bureau international des poids et mesures (BIPM) to the Secretary General of the ITU in 2000, a new question ITU-R 236/7 on The Future of the Coordinated Universal Time UTC time scale was gen erated by WP 7A in 2001. Question 236/7 was structured to address the future definition and use of UTC in the ITU-R. recommendations, and was updated over time [1], Major technical changes to UTC clearly have a potentially significant impact on communications networks, navigation systems, time/frequency distribution systems and virtually all aspects of civil/military timekeeping, In order to better conduct the often-difficult discussions, several events have taken place in the past, coordinated by the ITU, starting with a meeting at the BIPM in Sèvres in 2002, followed by a Colloquium on UTC in Turin in 2003. Then a draft revision of recommendation TF.460 submitted to Radiocommunication Assembly in 2012 (RA-12), which was unsuccessful due to lack of consensus. These were followed by the holding of an ITU-BIPM workshop in Geneva in 2013, preceded by the publication the same year in an ITU News magazine, of various opinions on the question of whether to abolish or not to abolish the leap second in UTC. As a result, divergent views on the evolution of UTC were clearly reflected in the Conference Preparatory Meeting (CPM) report to the World Radiocommunication Conference of 2015 (WRC-15). Things began to evolve in a convergent way after WRC-15, notably with the adoption by the Conférence générale des poids et mesures (CGPM) of two resolutions, one in 2018 On the definition of time scales and one in 2022 On the use and future development of UTC. In the meantime, a MoU was signed by the BIPM and the ITU in 2020. The work was complemented by the release of a substantial report on Time signals to be disseminated by radiocommunication systems [11], followed by the organization of a Special session with the BIPM on Resolution 655 (WRC- 15) during the 2nd ITU Inter-regional Workshop on WRC-23 Preparation, held in Geneva in 2022, Resulting from close collaboration between the BIPM and the ITU, key articles on the future of UTC were published in ITU News magazine in 2023 Indeed, the year 2023 was a significant and decisive year as the ITU unanimously succeeded in achieving the main objective of moving towards a continuous UTC when WRC-23, held in Dubai from 20 November to 15 December, endorsed the BIPM decision on this matter. This led to the revision of Resolution 655 (WRC-15), paving the way for further studies to be carried out by WP 7A, with a view to a possible revision of Recommendation TF.460 that is incorporated by reference in the Radio Regulations. It could potentially include a new code format for the continuous UTC signal to be disseminated and thus be able to end the process of inserting leap seconds into UTC at a date and for a maximum value of the UT1 - UTC difference that will both be defined in a CGPM Resolution in 2026. The medium-term objective of WP 7A on this topic is to complete the draft revision of Recommendation TF.460 and submit it to Study Group 7 for further consideration and approval, with a view to its subsequent adoption by the RA-27 and then by the WRC-27 to be held in 2027, thus implementing Resolution 655 (Rev.WRC-23).